Studies on Phenolase Enzymes in Prawns 1. The Distribution and Physical Properties of Phenolases in Penaid Prawns - ANTONY, P. D.; NAIR, M. RAJENDRANATHAN (Fishery Technology, 1968)
The distribution of phenolases in certain species of Penaeidprawns has been studied. Attempts were made to locate the regionsof maximum enzyme activity in the prawns. The relative dopaseactivity has been examined in extracts from head, tail, shell withcuticles and muscle. The head juice and tail extracts were found toregister very high order of enzymic activity. Metapenaeus affinis,Metapenaeus monoceros and Penaeus indicus record comparativelyhigher enzymic activity than Parapenaeopsis stylifera and Metapenaeusdobsoni, No definite relationship has been found between therelative activity of the enzyme and size grade at least in one speciesexamined. Experiments were done to determine the pH optima ofthe enzyme and the influence of pH on its deactivation. Exposure tohigher temperatures upto 55C was shown to activate the crudeenzyme considerably. The possible implications of the observationshave been discussed.